Analisis Perpindahan Gaya SideLoad Pegas Suspensi Tipe C Menggunakan Finite Element Method (FEM) - Sigit Setijo Budi; Firman Lukman Sanjaya; Faqih Fatkhurrozak; Syarifudin Syarifudin; Nur Aidi Ariyanto (Infotekmesin, 2023)
The suspension must provide comfort and safety to the vehicle. Therefore, it is necessary to analyze the load's effect on the pressure distribution on the axle so that the spring strength from the sideload force can be simulated. This study aims to analyze the sideload force of type C suspension springs using FEM. Spring variations are the number of different threaded coils, namely 11, 12, and 13. In the FEM simulation, the spring is given a load until 50mm, 100mm, 150mm, 200mm, and 250mm displacement occurs. The loading spreads to the X, Y, and Z axes. Each direction of the axis is measured by the pressure that occurs. The results showed that the pressure values that occur on the X, Y, and Z axes decreased with each increase in the number of screw coils. The lowest X-axis pressure reduction occurs in thread 12 at 63%. Meanwhile, the pressure on the Y axis decreased by 27% on the spring screw 12. The highest decrease in pressure on the Z axis occurred by 34% on the spring screw 12 compared to the spring screw 11.